A fatal endocarditis case due to an emerging bacterium: Moraxella nonliquefaciens. (2017) - Duployez, C.; Loïez, C.; Ledoux, G.; Armand, S.; Jaillette, E.; Wallet, F.
Highlights: Endocarditis due to Moraxella nonliquefaciens is rarely described. This bacterium belongs to the upper respiratory tract flora such as alpha-streptococci responsible of endocarditis. New identification methods such as MALDI-TOF allows us an easy identification of this microorganism, probably underestimated in systemic infections. Abstract: Moraxella nonliquefaciens is a Gram-negative coccobacillus considered as a commensal organism from the upper respiratory tract, with low pathogenic potential. The phenotypical conventional identification is difficult and the matrix-assisted laser desorption/ionization time-of-flight technology has increased the resolution of identification of this bacterium. We report a fatal case of endocarditis due to M. nonliquefaciens whose identification was confirmed by 16S rRNA, and we review the literature on this pathogen in endocarditis.